Bioresorbable vascular stents and drug-eluting stents in treatment of coronary heart disease: a meta-analysis - Ni, Le (J Cardiothorac Surg, 2020)
OBJECTIVE: To compare the efficacy and safety of bioresorbable vascular stents (BVS) and drug-eluting stents (DES) in coronary heart disease. METHODS: The full text of clinical studies involving BVS and DES was retrieved in PubMed, Springer, EMBASE, Wiley-Blackwell, and Chinese Journal Full-text Database. Review Manager 5.3 was used for meta-analysis to evaluate the risk of target lesion failure, stent thrombosis and cardiac death in BVS and DES. RESULTS: Finally, 10 studies with 6383 patients were included in the meta-analysis. Compared with DES group, BVS group had significantly increased risk of target lesion failure (OR = 1.46, 95%CI 1.20–1.79, P = 0.0002; P (Heterogeneity) = 0.68, I(2) = 0%), stent thrombosis (OR = 2.70, 95%CI 1.57–4.66, P = 0.0003; P (Heterogeneity) = 1.00, I(2) = 0%) and cardiac death (OR = 2.19, 95%CI 1.17–4.07, P = 0.01; P (Heterogeneity) = 0.93, I(2) = 0%). CONCLUSION: This study shows that DES is a safer treatment than BVS for coronary revascularization.